Burundi : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Modification of Performance Criteria; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burundi. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Second Review for Burundi under the three-year arrangement under the Poverty Reduction and Growth Facility (PRGF). All quantitative and structural performance criteria for March 2009 were met, and structural reforms are on track. In the near term, the authorities are determined to focus on sustaining macroeconomic stability, increasing domestic resource mobilization, promoting pro-poor growth, and implementing the power-sharing agreement to consolidate the peace process. Their commitment to the PRGF-supported program is unwavering and their end-March 2009 program performance has been impressive.